Novel microwave assisted sol-gel synthesis (MW-SGS) and electrochromic performance of petal like h-WO3 thin films - Kharade, Rohini R.; Patil, K. R.; Patil, P. S.; Bhosale, Popatrao N. (Materials Research Bulletin, 2012)
Use of domestic microwave oven is first time employed for chemical deposition of nanocrystalline hexagonal WO3 (h-WO3) thin films. Low cost precursors like sodium tungstate, hydrochloric acid, oxalic acid and potassium sulfate signifies cost effectiveness of this thin film fabrication route. Scanning electron microscopy images reveal formation of petal like nanodisks. A number of analytical techniques were used to characterize the WO3 petal like nanodisks, including X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX). X-ray photoelectron spectroscopy, FT-IR spectroscopy, Raman scattering spectroscopy, UV-visible spectrophotometry and cyclic voltammetry (CV). The X-ray photoelectron spectroscopic studies revealed 2.89 O/W atomic ratio. The electrical transport studies on WO3 thin films show semiconducting behavior with n-type semiconductivity. The value of determined coloration efficiency is 57.90 cm(2)/C. The mechanism of Li+ intercalation and deinercalation in h-WO3 matrix is proposed for enhanced electrochromism. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrochemical properties; Oxides; photoelectron spectroscopy